Entrepreneurship In The Qur'an From The Perspective Of Buya Hamkah Interpretation And Its Relevance To The Work Ethic Of Pt Amirah Indonesia Tour Employees - Nasution, Syamsul Bahri; Arifin, Zainal; Harahap, Mardian Idris (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Entrepreneurship in Islam has a strong foundation in the Qur'an, which encourages its people to work hard, earn a halal livelihood, and run a business with the values of honesty and responsibility. This study aims to analyze the concept of entrepreneurship in the Qur'an based on the perspective of Buya Hamka's interpretation and its relevance to the work ethic of employees of PT. Amirah Indonesia Tour, a company engaged in Umrah travel services and halal tourism. The method used in this study is qualitative-descriptive with a literature study approach to Tafsir Al-Azhar by Buya Hamka, as well as empirical data analysis regarding work culture at PT. Amirah Indonesia Tour. The results of the study show that Buya Hamka interprets entrepreneurship as an effort that is not only oriented towards material gains, but also emphasizes integrity, noble morals, and the balance of the afterlife. Values such as hard work, trust, and ihsan (doing your best) are the main pillars in running a successful business according to Buya Hamka. The relevance of entrepreneurial values in the Qur'an to the work ethic at PT. Amirah Indonesia Tour can be seen in the application of the principle of trust in customer service, innovation in service development, and commitment to maintaining Islamic work quality. Employees of PT. Amirah Indonesia Tour also applies spiritual values that support work productivity, such as discipline, responsibility, and the spirit of providing benefits to the people. This study concludes that the application of Islamic entrepreneurial principles according to Buya Hamka's interpretation can be a relevant guideline in building a professional work ethic and integrity in sharia-based companies. Research recommendations include strengthening training based on Islamic values, developing a more innovative work culture, and improving spiritual programs to support the balance of the afterlife in the work environment.